HTA CORE MODEL - R. I. Yagudina; T. Yu. Nor; A. D. Sevostyanov (Фармакоэкономика, 2015)
The EUnetHTA Core Model is an electronic system of standardized health technology assessment, currently under development by EUnetHTA. The system is designed to be used within the EUnetHTA program countries (which include Austria, Belgium, Denmark, Finland, Bulgaria, Croatia, Cyprus, Czech Republic, Estonia and others). The Core Model software is currently under development, along with research and reporting methods. The HTA Core Model aim is to create a single database on health technologies, which might be used for new technologies assessment wherever the program is applicable. HTA Core Model is based on the principal of dividing given information into standardized thematic chapters, organized from common to precise. By this, a common assessment technology for any health technology is created to make possible a maximum precise compartment of competing technologies by selected key values. Research, made by the HTA Core Model, are unified, and are mostly designed for health technology assessment in EU zone. For utilizing in healthcare environment beyond EU, they may be localized (completely or partly, depending on local healthcare detail).